EU outsourcing to the East, governance and innovation systems in the Baltic Countries: A three-stage approach - Jari Hyvärinen (The Research Institute of the Finnish Economy (ETLA), 2004)
This paper combines the features of outsourcing theory, the principal-agent model and institutional economics, and gives the guidelines how the firms in the Baltic countries might survive in the enlargened EU markets. Such guidelines are presented in three stages to demonstrate an institutional system framework connecting financial governance, the governance in production and the governance of innovation in order to enhance the principal and managerial incentives for higher innovative activity in the enlargened EU-Baltic industrial integration. – – Tämä paperi yhdistää ulkoistamisteorian, päämies-agenttimallin ja institutionaalisen taloustieteen tarjoamalla arvioita kuinka Baltian maiden yritykset selviävät laajenevilla EU:n markkinoilla. Nämä suuntaviivat esitetään kolmivaiheisena mallina demonstroimalla institutionaalinen järjestelmä, joka yhdistää rahoituksen, tuotannon ja innovaatioiden hallintojärjestelmät. Näiden tarkoituksena on kannustaa omistajia ja johtajia korostamaan innovaatioiden merkitystä laajenevassa EU:n ja Baltian maiden välisessä teollisuuden integraatiossa.
Keywords: 330; outsourcing; innovation system; institutions; governance; EU enlargement; ulkoistaminen; innovaatiojärjestelmä; instituutiot; hallinnointi; EU:n laajentuminen; Outsourcing; Innovation; EU-Erweiterung; Nordosteuropa; Governance-Ansatz